(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article explores the significant role that idioms play in the English language and communication as a whole. Idioms are more than just common phrases — they are expressions that capture the culture, history, and mindset of English-speaking communities. Through idioms, we gain insight into how people think, feel, and interpret the world around them. For instance, expressions like “a blessing in disguise” or “hit the nail on the head” reveal the creativity and practicality often found in English-speaking cultures. Understanding idioms is therefore crucial for language learners, as it not only enhances their vocabulary and comprehension but also helps them sound more natural and confident in conversation. Learning idioms allows learners to connect more deeply with the cultural essence of the language and to communicate with greater fluency and authenticity.